2010
DOI: 10.1002/cncr.25009
|View full text |Cite
|
Sign up to set email alerts
|

hsa‐miR‐210 is a marker of tumor hypoxia and a prognostic factor in head and neck cancer

Abstract: BACKGROUND:Hypoxia is an important mechanism of treatment resistance in head and neck squamous cell carcinoma (HNSCC). MicroRNAs are short noncoding RNAs that regulate multiple mRNAs and are frequently dysregulated in cancer. The authors have investigated the role of 3 microRNAs, including the hypoxia-induced hsa-miR-210, as potential markers of hypoxia or prognosis. METHODS: Three hypoxia-related microRNAs, hsa-miR-210, hsa-miR-21, and hsa-miR-10b, were measured in 46 samples from patients with HNSCC. Express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(167 citation statements)
references
References 36 publications
7
157
1
1
Order By: Relevance
“…In contrast to our study, miR-210 was reported to be upregulated in breast cancer, pancreatic tumors, and head and neck cancer and to be correlated with their poor outcome (21)(22)(23)(24). Moreover, previous studies have shown that miR-210 inhibits apoptosis and bypasses cell cycle arrest in cancer cell lines such as MCF-7 and HCT116 Dicer ex5 cells (25,26).…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast to our study, miR-210 was reported to be upregulated in breast cancer, pancreatic tumors, and head and neck cancer and to be correlated with their poor outcome (21)(22)(23)(24). Moreover, previous studies have shown that miR-210 inhibits apoptosis and bypasses cell cycle arrest in cancer cell lines such as MCF-7 and HCT116 Dicer ex5 cells (25,26).…”
Section: Discussioncontrasting
confidence: 92%
“…Concerning the importance of histological variant in ACC clinical outcome, we have confirmed the results of a retrospective survival analysis provided by Wong et al [26], in which was shown a better prognosis for malignant adrenocortical neoplasm showing predominant oncocytic features in comparison with those of classical type. The prognostic value of miR-210 has already been demonstrated in breast [33], pancreatic [34], head and neck carcinomas [35], pediatric osteosarcoma [36], and glioblastoma [37].…”
Section: Differential Expression Of Mirnas Investigated In Adenoma Vsmentioning
confidence: 96%
“…miRNA appears to be a reliable biomarker for diagnosis, prognosis, and treatment evaluation in different types of cancers. [40][41][42] miRNA expression profiles could be used to define the cell types, [2,3] thereby allowing detection of the miRNA biomarker or expression signatures from patients in order to develop individualized therapeutic plans, possibly even targeting specific miRNAs for a given patient. Furthermore, the understanding of how an individual's genetic inheritance of miRNA polymorphisms affects the body's response to certain drugs will be key to creating drugs with greater efficacy and safety.…”
Section: Individualized Therapymentioning
confidence: 99%